DINAMIKA PSIKOLOGIS PENILAIAN KEADILAN - - Faturochman; Djamaludin Ancok (Faculty of Psychology, Universitas Gadjah Mada, 2001)
The heuristic theory of justice proposes that earlier information and judgment affect the later judgment. If the earlier information and judgment is of procedure it will affect the judgment of distributive fairness. In contrast, if the earlier information and judgment is distributive fairness judgment it will affect the judgment of procedural fairness. This study shows that the influence of earlier information and fairness judgment is effective if it is procedural matter. The effect of distribution and distributive fairness judgment on procedural fairness judgment is not significant. Keywords: procedural fairness, distributive fairness, heuristic.